HUBUNGAN SUHU PERMUKAAN LAUT DAN KLOROFIL-A BERDASARKAN CITRA SATELIT DENGAN HASIL TANGKAPAN IKAN PELAGIS KECIL DI PERAIRAN CILACAP - , AKHMAD WIRA PERDANA; , Ir. Supardjo S.D, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this study was to determine the distribution of sea surface temperature (SST) and chlorophyll-a content in Cilacap water using satellite imagery data, and to determine the relationship between sea surface temperature and chlorophyll-a content to the catches of small pelagic fish. The data of sea surface temperature and chlorophyll-a was found from Aqua MODIS satellite imagery during the period January 2010 - December 2012. Data catches of small pelagic fish of Cilacap water was obtained from the Department of Marine and Segara Anakan Resources Management Area. Satellite image data was processed by the software ENVI 4.8 and Arc GIS, to obtain the average value and distribution of images each month of sea surface temperature and chlorophyll content. Analysis of the data used in this study using descriptive analysis and by using tables and graphs to see seasonal trends and the relationship between sea surface temperature, chlorophyll-a, and the catch of small pelagic fish. During West Season the sea surface temperature range from 28,46Â° C to 30,78Â° C, in Transition Season I range from 28,58Â° C to 31,19Â° C, in East Season range from 25,47Â° C to 29,23Â° C, and in Transition Season II range from 25,26Â° C to 29,18Â° C. The average value of sea surface temperature at the time of the East Season (27,12Â° C) and Transition Season II (27,39Â° C) value is lower than the West Season (29,75Â° C) and Transition Season II (29,76Â° C). The average value of chlorophyll-a in East Season was 0,2286 mg/mÂ³ (range from 0,0699 â 0,4019 mg/mÂ³) and Transition Season II was 0,2048 mg/mÂ³ (range from 0,0790 â 0,4019 mg/mÂ³) that was higher than during the West Season was 0,1202 mg/mÂ³ (range from 0,0919 â 0,1462 mg/mÂ³) and Transition Season I was 0,1257 mg/mÂ³ (range from 0,0830 â 0,1640 mg/mÂ³). The Declining in sea surface temperatures caused increasing the chlorophyll-a, followed by the increasing of fish catches. The East Season and Transition Season II was more fertile than the others season, that need to be informed to fisherman.